Diversifying productive structures and improving access to finance in the Caribbean (2012)
Presents a synosis of the proceedings at the second Caribbean Development Roundtable (CDR) . Looks at the constraints faced by countries in the Caribbean in financing their economic adjustment after the crisis and seeks to suggest a few measures which the region should take in order to increase financing.
Keywords: FINANCING